A novel approach for locating mice brain regions of Cryptococcus neoformans CNS invasion - Chunting He; Qingfen Chen; Longkun Zhu (Bangladesh Pharmacological Society, 2016)
Aim of this study was to locate the brain regions where Cryptococcus interact with brain cells and invade into brain. After 7 days of intratracheal inocula-tion of GFP-tagged Cryptococcus neoformans strains H99, serial cryosections (10 ?m) from 3 C57 BL/6 J mice brains were imaged with immunofluorescence microscopy. GFP-tagged H99 were found in some brain regions such as primary motor cortex-secondary motor cortex, caudate putamen, stratum lucidum of hippocampus, field CA1 of hippocampus, dorsal lateral geniculate nucleus, lateral posterior thalamic nucleus, laterorostral part, lateral posterior thalamic nucleus, mediorostral part, retrosplenial agranular cortex, lateral area of secondary visual cortex, and lacunosum molecular layer of the hippocampus. The results will be very useful for further exploring the mechanism of C. neoformans infection of brain.